Stigma Identity Concealment in Hybrid Organizational Cultures. (June 2017) - Lyons, Brent J.; Zatzick, Christopher D.; Thompson, Tracy; Bushe, Gervase R.
Abstract : Previous stigma identity management theory has considered organizational cultural pressures as unitary in either supporting or discouraging open identity expression, leading individuals to either disclose or conceal their identities, respectively. However, within many organizations are cultures with opposing demands for how individuals should express their stigmatized identities. We integrate theory on stigma identity management and institutional logics to develop expectations about how individuals with stigmatized identities manage their identities in organizational cultures with opposing demands for identity expression, namely, organizational cultures that are informed by both supportive and unsupportive logics. We consider how configurations of supportiveness–unsupportiveness, along dimensions of logic centrality and logic compatibility, affect stigma holders' identity management choices and their well‐being and job performance. We argue that the consequences of affirming (e.g., disclosure) and distancing (e.g., concealing) identity management strategies vary depending on whether stigma holders comply with or resist against these hybrid configurations.